Nur77 and PPARγ regulate transcription and polarization in distinct subsets of M2-like reparative macrophages during regenerative inflammation - Garabuczi, Éva; Tarban, Nastaran; Fige, Éva; Patsalos, Andreas; Halász, László; Szendi-Szatmári, Tímea; Sarang, Zsolt; Király, Róbert; Szondy, Zsuzsa (Frontiers in Immunology, 2023)
Macrophage polarization is a process whereby macrophages develop a specific phenotype and functional response to different pathophysiological stimuli and tissue environments. In general, two main macrophage phenotypes have been identified: inflammatory (M1) and alternatively activated (M2) macrophages characterized specifically by IL-and IL-10 production, respectively. In the cardiotoxin-induced skeletal muscle injury model bone marrow-derived macrophages (BMDMs) play the central role in regulating tissue repair. Bone marrow-derived monocytes arriving at the site of injury differentiate first to M1 BMDMs that clear cell debris and trigger proliferation and differentiation of the muscle stem cells, while during the process of efferocytosis they change their phenotype to M2 to drive resolution of inflammation and tissue repair. The M2 population is formed from at least three distinct subsets: antigen presenting, resolution-related and growth factor producing macrophages, the latest ones expressing the transcription factor PPAR Nuclear receptor subfamily 4 group A member 1 (NR4A1; also termed Nur77) transcription factor is expressed as an early response gene, and has been shown to suppress the expression of pro-inflammatory genes during efferocytosis. Here we demonstrate that (1) Nur77 null BMDMs are characterized by elevated expression of PPAR resulting in enhanced efferocytosis capacity; (2) Nur77 and PPARregulate transcription in different subsets of M2 skeletal muscle macrophages during muscle repair; (3) the loss of Nur77 prolongs M1 polarization characterized by increased and prolonged production of IL-1by the resolution-related macrophages normally expressing Nur77; whereas, in contrast, (4) it promotes M2 polarization detected via the increased number of IL-10 producing CD206+ macrophages generated from the PPAR-expressing subset.